PUBLIC PREFERENCE FOR MICRO WAQF BANKS: AN EFFORT TO INCREASE COMMUNITY BUSINESS - Arroyyan Ramly; Amrizal Hamsa (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
The Islamic financial literacy index in Aceh is still relatively low at 18.64% compared to the conventional financial literacy index. The purpose of this study is to analyze the level of preference of Acehnese people towards micro Waqf Banks. The presence of micro Waqf banks in Aceh seeks to improve the welfare of urban and rural communities. Quantitative method with multiple regression analysis techniques is used to study those variables. The source of data obtained is the primary source through distributing questionnaires to 100 respondents throughout Aceh. The variables used in this research are literacy index, preference, religiosity, and business motivation. The results indicate that the preference, religiosity, and business motivation have a positive and significant effect   on Islamic financial literacy with the prob value. 0.00 < = 0.05. the coefficient of determination shows a value of 0.9900, or 99.00 % which means that all dependent variables have a significant effect on islamic financial literacy while the rest are influenced by other variables. Regarding  the fact that Islamic financial literacy for micro waqf banks is 52% as well as the role of microwaqf banks support in  increasing micro-scale businesses in the community, public preference for micro waqf banks is still low compared to Islamic banks. Therefore the implications of this research have a positive impact on the community and academics in suggesting to continue  supporting the emerging of sharia-compliant businesses by utilizing micro waqf banks.